Effect of Maternal Age and Fetal Number on the Risk of Hypertensive Disorders of Pregnancy - Smith, Devin D.; Merriam, Audrey A.; Jung, Julley; Gyamfi-Bannerman, Cynthia (American Journal of Perinatology, 2018)
Objective Our primary objective was to compare the differential contribution of fetal number and maternal age to the risk of hypertensive disorders of pregnancy (HDP).Study Design This was a secondary analysis of a large study of primary cesarean delivery. Women with singleton, twin, or triplet gestations were included. Women were divided into groups based on fetal number and maternal age. The primary outcome was HDP. A logistic regression model was fit to adjust for confounders. The incidence of HDP was compared with the reference group and within exposure groups.Results Of the 70,417 women included, HDP occurred in 8,079 (12%) women. The frequency of HDP among the comparison groups ranged from 11 to 38%. Nearly all groups had significantly increased risk of HDP compared with young maternal age singletons. Twin and triplet gestations increased the risk of HDP over singletons irrespective of maternal age after adjusting for baseline disease and race. The risk of HDP did not significantly increase with maternal age when fetal number was similar.Conclusion Fetal number significantly increased the risk of HDP and contributed more to that risk than maternal age. Maternal age became significant in groups with age greater than 40 years.
Keywords: gestational hypertension; preeclampsia; advanced maternal age; multiple gestation; multifetal gestation; twins; triplets; hypertensive disorders of pregnancy